2023
DOI: 10.1002/htj.22981
|View full text |Cite
|
Sign up to set email alerts
|

The effect of triangular shutter type flow deflector perforated baffle plate on the thermofluid performance of a heat exchanger

Md. Atiqur Rahman

Abstract: The study aimed to investigate the heat transfer (HT) properties of a tubular heat exchanger (HX) by using innovative baffle plate arrangements. The newly designed baffle plate was circular with triangular openings and adjustable triangular flow deflectors. These deflectors were strategically placed at the inlet of the HX to create a swirling flow downstream. Three baffle plates were installed along the flow direction with different length‐to‐diameter ratios (pitch ratios) to assess their impact on HT, pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The ratio of the enhancement rate indicating the surge in HT to f is known as THP. Equations and present the primary criteria for evaluating the THP of the thermal system. Models above a THP of 1 are considered advantageous, whereas models below this threshold are deemed unfavorable. The flow and thermal characteristics of nanofluids play a crucial role in evaluating and enhancing their performance.…”
Section: Nanofluids: Fundamentals Synthesis Stability and Propertiesmentioning
confidence: 99%
“…The ratio of the enhancement rate indicating the surge in HT to f is known as THP. Equations and present the primary criteria for evaluating the THP of the thermal system. Models above a THP of 1 are considered advantageous, whereas models below this threshold are deemed unfavorable. The flow and thermal characteristics of nanofluids play a crucial role in evaluating and enhancing their performance.…”
Section: Nanofluids: Fundamentals Synthesis Stability and Propertiesmentioning
confidence: 99%
“…In another analysis, 36 he utilized two 16 rectangular shutter-type flow deflectors to induce turbulence, resulting in a 1.17 improvement in thermal efficiency when PR was 1 and α was 30. Furthermore, Rahman 37 conducted further research on the impact of triangular shutter-type flow deflector baffle plates, which showed an additional improvement in the thermal efficiency of the HX.…”
Section: Introductionmentioning
confidence: 99%